A QUALITATIVE EXPLORATION OF CORPUS AND CHATGPT INTEGRATION IN HOSPITALITY ENGLISH LEARNING - Andi Rizki Fauzi (Institut Pendidikan Tapanuli Selatan, 2026)
English speaking proficiency remains a critical challenge for Indonesian hospitality students, with vocabulary limitations, pronunciation difficulties, and speaking anxiety significantly hindering their professional readiness. While corpus linguistics and artificial intelligence offer promising pedagogical affordances, limited research examines their integrated application in ESP contexts. This qualitative study explored hospitality students' lived experiences integrating corpus-based learning with ChatGPT for speaking development, investigating both affordances and constraints of this pedagogical approach. Semi-structured interviews were conducted with eleven hospitality students at STIPARY Tourism Academy Yogyakarta who engaged in an eight-week integrated corpus-ChatGPT intervention. Thematic analysis using QdA Miner Lite software identified six major themes addressing research questions regarding student experiences, integration strategies, and perceived benefits. Findings revealed that corpus consultation provided authentic language exposure and contextual awareness, though information overload challenged lower-proficiency learners. ChatGPT facilitated interactive practice, immediate feedback, and anxiety-free experimentation, despite technical limitations and reliability concerns. Students employed diverse integration strategies—sequential, reverse, and dialogic—creating personalized learning ecosystems. Perceived benefits included confidence enhancement, vocabulary expansion, fluency development, and grammatical awareness, with successful transfer to hospitality-specific tasks. The integrated approach effectively addresses multidimensional speaking competencies by combining corpus authenticity with ChatGPT interactivity. However, successful implementation requires proficiency-differentiated scaffolding, explicit strategy instruction, reliable technical infrastructure, and positioning AI as preparation for authentic human communication rather than replacement.